The life of the heroin user typical beginnings, trajectories and outcomes - Darke, Shane (International research monographs in the addictions, 2011)
Heroin is a worldwide scourge and a seemingly intractable one. The Life of the Heroin User: Typical Beginnings, Trajectories and Outcomes is the first book to apply a biographical approach to the lifecycle of the heroin user from birth until death. Chapters address each stage of the user's life, including childhood, routes to use, the development of dependence, problems arising from addiction, death and options for treatment and prevention. Drawing on over two decades of experience in the field of opiate research, Shane Darke examines major theoretical approaches to the development of opiate dependence and the efficacy of treatment options for opiate dependence. Key points are presented at the end of each chapter. The most detailed review available of what is likely to happen to the dependent heroin user, this is an important book for clinicians, researchers and students in the fields of drug and alcohol studies and public health